Product Quality, Price, and Consumer Knowledge as Determinants of Cajuput Oil Purchasing Decisions - Solissa, Anita; Setitit, Ignasius; Renyut, Selvia F. G. (JIMAD : Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the influence of product quality, price, and consumer knowledge on purchasing decisions of cajuput oil in Unet Village, Fena Fafan District, Buru Regency. The research employed a quantitative approach, with data collected through questionnaires distributed to consumers who have purchased local cajuput oil. The results indicate that product quality has a significant influence on purchasing decisions, followed by consumer knowledge and price. These findings emphasize that consumers prioritize product quality and the information they possess when making purchasing decisions, while price remains a consideration but is not the main factor. This study recommends improving product quality, educating consumers, and setting prices that reflect the value offered as strategies to increase buying interest.